Operando ZnO recrystallization for efficient quantum-dot light-emitting diodes - Song Wang; Shihao Liu; Ting Wang; Jialin Bai; Jingyu Peng; Hanzhuang Zhang; Wenfa Xie; Wenyu Ji (Light: Science & Applications)
Abstract ZnO nanoparticles (NPs) play a crucial role in advancing quantum-dot light-emitting diodes (QLEDs) because of their excellent electron transport properties. While the conductivity of ZnO is determined by both the density and mobility of charge carriers, a previously overlooked problem is that excessive carrier density in ZnO can lead to nonradiative Auger recombination at the quantum-dot/ZnO interface. An ideal electron transport layer should possess both high mobility and low carrier density. Here, we achieve such transport properties in ZnO NP films through operando recrystallization, a process triggered by the diffusion of Al ions from the cathode under acidic conditions. This diffusion induces the coalescence of neighboring ZnO NPs, forming defect-passivated, long-range ZnO crystals. When used as the electron transport layer in QLEDs, recrystallized ZnO NPs enhance the external quantum efficiency from 17.2% to 33.7% compared with devices with conventional ZnO electron transport layers. These findings offer valuable insights into the development of charge transport materials for high-performance optoelectronic devices.